Fachada de casa de material noble - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: La fotografía muestra la fachada de una casa de material noble con dos niños en la vereda con uniformes escolares.
ENGLISH: The photograph shows the facade of a house made of noble material with two children on the sidewalk in school uniforms.

SPANISH: La fotografía muestra la fachada de una casa de material noble con dos niños en la vereda con uniformes escolares.
ENGLISH: The photograph shows the facade of a house made of noble material with two children on the sidewalk in school uniforms.
House facade made of noble material
Keywords: Iquitos (Perú)|~|Catholic Institutions|~|Catholic schools|~|Catholic priests|~|Iquitos (Perú)|~|Instituciones Católicas|~|Escuelas Católicas|~|Sacedote Católica